Desacralization of Marriage in the Islamic Community of Javanese Farmers - Sardjuningsih, Sardjuningsih (UIN Sunan Kudus, 2020)
Field research with a phenomenological approach, in the District of Kabuh-Jombang. The barren rural socio-geographical setting makes tradition basics a reference and measure of norms of action. The uniqueness of this study with previous research is the process of reducing the sacredness of marriage by placing the status of Widower or Widow better than the status of an old spinster or old age. Research with a Phenomenological approach with Robert Merton's Structural-Functional analysis knife rests on deep interview techniques of 20 informants consisting of couples who experience young and divorced couples, families, and community leaders. produce conclusions that the tradition of underage marriage is a social fact, a habit that still continues to this day, constructed with noble and sacred meaning. In the social process the Nobleness of meaning is not supported by other social facts, that being a widower or widow is better than being an old woman or old woman. This puts divorce better than maintaining marriage. This pragmatic outlook is contrary to the ideal ideals of a sacred marriage. The result of a complex divorce is a negative new social fact that is neglecting the rights of children to be paid by their parents. This negative social fact is due to the dysfunctional social control and social structure of the process of adaptation to change.